Proceedings of the Ninth ACM International Conference on Interactive Tabletops and Surfaces 2014
DOI: 10.1145/2669485.2669500
|View full text |Cite
|
Sign up to set email alerts
|

HuddleLamp

Abstract: We present HuddleLamp, a desk lamp with an integrated RGB-D camera that precisely tracks the movements and positions of mobile displays and hands on a table. This enables a new breed of spatially-aware multi-user and multi-device applications for around-the-table collaboration without an interactive tabletop. At any time, users can add or remove displays and reconfigure them in space in an adhoc manner without the need of installing any software or attaching markers. Additionally, hands are tracked to detect i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 42 publications
0
70
0
Order By: Relevance
“…The concept of spatial distribution has recently been taken further by using digital devices that are combined to enable crossdevice interactions [28,29]. For example Rädle et al [28] presented HuddleLamp, a desk lamp with an included camera, that allows for seamless tracking of positions of mobile devices on a desk as well as hands working on them.…”
Section: From Paper To Interactive Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of spatial distribution has recently been taken further by using digital devices that are combined to enable crossdevice interactions [28,29]. For example Rädle et al [28] presented HuddleLamp, a desk lamp with an included camera, that allows for seamless tracking of positions of mobile devices on a desk as well as hands working on them.…”
Section: From Paper To Interactive Devicesmentioning
confidence: 99%
“…For example Rädle et al [28] presented HuddleLamp, a desk lamp with an included camera, that allows for seamless tracking of positions of mobile devices on a desk as well as hands working on them. Results of an evaluation showed that participants are capable of working on multiple surfaces and prefer spatially-aware gestures to manage information transfer and device linkage [29].…”
Section: From Paper To Interactive Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research explored the spatial relationships of devices (e.g. [2,8,15]), cross device interactions which support changing numbers of devices (e.g. [4,8]), the use of personal devices to bring in information (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…[2,8,15]), cross device interactions which support changing numbers of devices (e.g. [4,8]), the use of personal devices to bring in information (e.g. [12]), as well as body worn devices in concert with wall displays (e.g.…”
Section: Related Workmentioning
confidence: 99%